Strategi Fundraising Wakaf Harta Benda Oleh Pesantren Tebuireng Terhadap Perkembangan Pesantren (Studi Yayasan KH. M. Hasyim As’ari Tebu Ireng 2020-2023) - Assalafy, Chotibul Umam; Basalamah, Muhammad Ridwan; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Tebuireng Islamic Boarding School is one of the Islamic boarding schools with one of the exemplary Islamic boarding schools for other Islamic boarding schools. One of them is an example with good waqf management. Since the establishment of the Tebuireng Islamic boarding school which was founded by KH. M. Hasyim Asy'ari in 1899 AD. Already had a picture for the management of waqf in the future, after the regeneration of the change of caretakers until the time of KH. Salahuddin Wahid with the development period continued by the current caretaker, namely KH. Abdul Hakim Mahfudz or commonly called Gus Kikin continued the development of the Islamic boarding school. This study aims to see the waqf fundraising strategy in the Tebuireng Islamic boarding school during the leadership of Gus Kikin, and also to find out the extent of the waqf management carried out for the development of the Islamic boarding school. From the results of the research conducted, there are strategies carried out by the Tebuireng Islamic boarding school during the leadership of Gus Kikin, namely: Development of Islamic boarding schools, effectiveness of waqf, and improvement of educational and study institutions. Of the three strategies carried out, the results will automatically be seen by the community and alumni and guardians of students, which will raise interest in the investment of the afterlife in the form of waqf. The strategy is with the productive waqf version of Tebuireng. In addition, the utilization of waqf carried out by the Tebuireng Islamic boarding school is to create buildings and institutions to reserve damaged items and reuse them, such as chairs and study tables in existing educational institutions.. Keywords: Waqf Strategy, Tebuireng Waqf, Tebuireng Islamic Boarding School, Fundraising